Pengelolaan Keuangan Mahasiswa Akuntansi Universitas Dian Nuswantoro : dilihat dari sisi Literasi Keuangan dan Gaya Hidup - Abelinno Rizky Sectioazhari; Enny Susilowati Mardjono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to find out and analyze the influence of Financial Literacy and Lifestyle on the Financial Management of Accounting Students at Dian Nuswantoro University. In this research, the data source used is primary data. The population of Accounting students at Dian Nuswantoro University class 2021/2022 semester 6 is 130 people and the sample obtained by this research is 120. Data analysis in this study used a multiple linear regression analysis model. The sampling technique used in this research used purposive sampling. The results of this study show that lifestyle has an effect on financial management and financial literacy has no effect on financial management.